1975
DOI: 10.1295/polymj.7.558
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Solution of Bisphenol A Polycarbonate

Abstract: ABSTRACT:Narrow-distribution fractions of bisphenol A polycarbonate in tetrahydrofuran (THF) and chloroform were studied by light-scattering, sedimentation velocity, and viscosity measurements over the range of molecular weights from 4x 103 to 5x 10 5 • The asymptotic values of a dimensionless quantity A2Mwl[r;] and the interpenetration function lJf where significantly lower than those usually expected for flexible polymers, suggesting a certain stiffness of the polycarbonate chain. Here A2 is the second viria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…In this case, the value of -(2qML}1 12 g(d/2q) also may be determined from the initial slope of the plot together with the <Poo value so obtained. As a necessary fourth relation, we propose, in accordance with Tsuji,et al,5 Polymer J., Vol. 9, No.…”
Section: Methods Of Analysissupporting
confidence: 69%
See 2 more Smart Citations
“…In this case, the value of -(2qML}1 12 g(d/2q) also may be determined from the initial slope of the plot together with the <Poo value so obtained. As a necessary fourth relation, we propose, in accordance with Tsuji,et al,5 Polymer J., Vol. 9, No.…”
Section: Methods Of Analysissupporting
confidence: 69%
“…The data points for each fraction follow a linear relation represented by 12 ( 5) It is to be observed that two sets of plotted points, one from the peak method and the other from the Baldwin method, fall on a single line, as should be expected. Table V summarizes the values of s0 and ks for all the fractions that were subjected to sedimentation velocity experiments.…”
Section: Sedimentation Coefficientsupporting
confidence: 54%
See 1 more Smart Citation
“…The high l p (6.0 nm) relative to the contour length (16.9 nm) of atactic PPMO also indicates the abnormal linearity of its main chain. The l p value of PPMO is much larger than that of various ordinary synthetic polymers such as polystyrene ( ca 0.9 nm), poly(α‐methylene‐γ‐butyrolactone) ( ca 0.9 nm), bisphenol A polycarbonate ( ca 1.8 nm) and poly(1‐phenyl‐1‐propyne) ( ca 3.8 nm) . Furthermore, the l p of PPMO is comparable to that of polysaccharides such as alginate ( ca 9 nm) and single‐stranded deoxyribonucleic acid ( ca 2.5 nm) despite the chemical structure of PPMO without any functional moieties such as polar substituents.…”
Section: Resultsmentioning
confidence: 93%
“…Here, E was estimated from the slope of the tangent (red lines). The black dots are derived from the form factor for the Gaussian coil model (0.02 − 0.1 nm −1 ), fuzzy spheres model (0.1 − 1.1 nm −1 ) and wormlike chain model (1.1 − 3.0 nm −1 ) in the relevant regions. The peak at 4.5 nm −1 corresponds to the helical pitch of stereoregular PPMO (and discussed in detail in the main text).…”
Section: Resultsmentioning
confidence: 99%